A low-cost ZigBee-based wireless industrial automation system - Castro, Pedro Filipe Mendes de (2017)
This paper describes the development of an industrial automation system based on a ZigBee wireless sensor network, designed for the monitoring and control of multiple refrigeration equipments in an industrial area, replacing the existing cabled network, which is based on the LonWorks platform. For this purpose, ZigBee routers were used to replace the local controllers at the refrigeration equipments, while the central management controller was re-placed by a ZigBee coordinator and a PC. The proposed system was devel-oped using a hardware platform based in the CC2530 integrated circuit and the Z-Stack software. Results from experimental field tests performed in an industrial environment are provided in order to assess the performance of the developed ZigBee network.